Otroci s posebnimi potrebami v šolskem prostoru - Vovk Ornik, Natalija (Šolska knjižnica, 2014)
Teaching professionals at today's school face an ever more diverse student population. Because of this we present some important teaching issues which are relevant when teaching children with special needs at primary and secondary school. All teachers who have children with special needs among their students, should know legalisation in the area of teaching children with special needs. The paper presents the most important information in this area which is closely related to the usefulness of certain legal provisions and can as such be of help to professionals.
Keywords: otroci s posebnimi potrebami; šolski prostor; šolski sistem; usmerjanje; zakonodaja